Graphene zeolite-based granular media filtration system for the pretreatment of brackish water - Pinto, Ma. Manna Farrel B.; Vasquez, Magdaleno R. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2019)
Desalination technologies continue to be of major research interest due to the enormous benefits it provides. However, fouling has been one of the major drawbacks of using membrane desalination technologies for commercial applications. In order to address this, a mechanistic study employing coagulation and granular media filtration was performed to evaluate the efficiency of a pretreatment system designed for brackish water. To obtain optimum conditions based on water quality parameters (Turbidity, Conductivity, Salinity, TDS and Dissolved Oxygen), optimization runs were conducted with varying coagulant dosage, pH and filter media configurations. Using ferric chloride (FeCl3) as coagulant and the coupling of exfoliated graphene and natural zeolite as filter media, optimum conditions of pretreatment were determined to be with a dosage of 10 ppm FeCl3 at pH 10 in the graphenezeolite-based columns. Under these conditions, the removal efficiencies ranged from 30 to 99%. Raman Spectroscopy data revealed structural changes in the zeolite and carbon-based filter media wherein adsorption was the dominant mechanism in the treatment process. This was further confirmed by laser microscopy imaging and topological analysis through morphological and roughness profile differentiation. X-ray fluorescence data also revealed elemental compositions of the samples before and after the two-stage treatment exhibiting adsorbed fouling species and other heavy metals from the synthetic and raw brackish water. Results indicated the effectiveness of the combined graphene-zeolite filter media in mitigating membrane fouling and pretreating brackish water as feed for membrane desalination processes.
Thesis (Master of Science in Environmental Engineering)--University of the Philippines Diliman
Keywords: Feed-water purification; Zeolites; Graphene